Current and Future Applications of Genetic, Archaeological, and Ethnobotanical Data to Uncovering Avocado Domestication - Wann, Kevin W.; Thakar, Heather B. (Ethnobiology Letters, 2024)
The domestication of fruit trees is a topic of increasing significance in anthropological research. The avocado is a perennial fruit domesticated in Central America with a complex history of management and dispersal since the arrival of humans in the New World. Archaeological data illustrates the avocado’s domestication from wild to cultivar forms throughout the Holocene, while genetic and ethnobotanical evidence provide insights into ancient avocado cultivation patterns. It is only through the combined application of all three lines of evidence that we may fully understand the dynamic origins of this essential fruit.